Word in Education: Good, Bad and Other Word - David Thomas Carr (Ignatianum University Press, 2020)
St John's Gospel identifies logos, translated as English 'Word', as the divine source of the wisdom or truth of the Christian message, if not with the godhead as such. However, given the cultural and intellectual influence of Greek thought on early Christian literature, one need not be surprised that these (and other) theological or metaphysical associations of Word are almost exactly replicated and prefigured in the dialogues of Plato, for whom formation of the divine aspect or element of human soul clearly turned upon access to or participation in the wisdom of logos. This paper explores the moral and spiritual connections between logos or Word, reason and soul in such Platonic dialogues as Gorgias, Republic and Theaetetus as well as the implications of conceiving education as the pursuit of such Word for ultimate human flourishing.